2014
DOI: 10.1001/jama.2014.5220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endoscopic Sphincterotomy for Suspected Sphincter of Oddi Dysfunction on Pain-Related Disability Following Cholecystectomy

Abstract: IMPORTANCE Abdominal pain after cholecystectomy is common and may be attributed to sphincter of Oddi dysfunction. Management often involves endoscopic retrograde cholangiopancreatography (ERCP) with manometry and sphincterotomy. OBJECTIVE To determine whether endoscopic sphincterotomy reduces pain and whether sphincter manometric pressure is predictive of pain relief. DESIGN, SETTING, AND PATIENTS Multicenter, sham-controlled, randomized trial involving 214 patients with pain after cholecystectomy without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
121
2
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(136 citation statements)
references
References 40 publications
(45 reference statements)
1
121
2
12
Order By: Relevance
“…67 However, a recent NIH study (EPISOD: evaluating predictors and interventions in sphincter of Oddi dysfunction) has shown that true sphincterotomy is no better than sham sphincterotomy in patients with post-cholecystectomy pain, so that the old concept of SOD Type III is now considered more like functional than biliary related, and endoscopic retrograde cholangiopancreatography approaches are no longer appropriate in that context. 68 Furthermore, most patients with SOD Type I have organic stenosis (eg, stones, stricture, pancreatitis, and pancreatic tumor) rather than motility disturbance of the sphincter, and biliary sphincterotomy is recommended; however not in this biliary classification. Therefore, Rome IV now recommends using the term suspected functional biliary sphincter of Oddi disorder for patients with prior SOD Type II only.…”
Section: Gallbladder and Sphincter Of Oddi Disordersmentioning
confidence: 99%
“…67 However, a recent NIH study (EPISOD: evaluating predictors and interventions in sphincter of Oddi dysfunction) has shown that true sphincterotomy is no better than sham sphincterotomy in patients with post-cholecystectomy pain, so that the old concept of SOD Type III is now considered more like functional than biliary related, and endoscopic retrograde cholangiopancreatography approaches are no longer appropriate in that context. 68 Furthermore, most patients with SOD Type I have organic stenosis (eg, stones, stricture, pancreatitis, and pancreatic tumor) rather than motility disturbance of the sphincter, and biliary sphincterotomy is recommended; however not in this biliary classification. Therefore, Rome IV now recommends using the term suspected functional biliary sphincter of Oddi disorder for patients with prior SOD Type II only.…”
Section: Gallbladder and Sphincter Of Oddi Disordersmentioning
confidence: 99%
“…7 The only study evaluating the value of both biliary and pancreatic manometry (in patients mostly classified as SOD type III) showed that neither were predictive of the outcome of sphincterotomies. 3 It would be helpful to have similarly stringent studies of dual manometry in patients with SOD type II. The putative gold standard loses even more credibility when we examine reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…3 They were aged 18 to 65 years, had burdensome pain more than 3 months after cholecystectomy, and fit the criteria of SOD type III. Patients underwent ERCP by experienced endoscopists, under conscious sedation, modified or full anesthesia, based on local practice.…”
Section: Methodsmentioning
confidence: 99%
“…Neither biliary nor dual biliary and pancreatic sphincterotomy provided sustained pain relief compared to sham therapy. Furthermore, abnormal manometric findings failed to predict treatment success [8]. Post-ERCP pancreatitis occurred in 11 % of patients in the sphincterotomy group despite prophylactic pancreatic stenting [8].…”
mentioning
confidence: 99%